Cardiac structure and function in elite Para-cyclists with spinal cord injury - Kim, J. H.; Trilk, J. L.; Smith, R.; Asif, I.; Maddux, P. T.; Ko, Y.-A.; Emery, M. S. (Medicine & Science in Sports & Exercise, 2016)
Purpose: We sought to explore the association between the spinal cord injury (SCI) level on the cardiac structure and the function observed in elite para-cyclists.